An independent, replicable, functional and significant risk variant block at intron 3 of CACNA1C for schizophrenia. (April 2022) - Wang, Zuxing; Chen, Wenzhong; Cao, Yuping; Dou, Yikai; Fu, Yingmei; Zhang, Yong; Luo, Xingqun; Kang, Longli; Liu, Na; Shi, Yun Stone; Li, Chiang-shan R; Xu, Yifeng; et al.
Objectives: Genome-wide association studies have identified a significant risk gene, CACNA1C, for schizophrenia. In this study, we comprehensively investigated a large set of CACNA1C single-nucleotide polymorphisms (SNPs) to identify the replicable risk alleles for schizophrenia and explore their biological functions. Methods: One Jewish (1044 cases vs 2052 controls), one European (1350 cases vs 1378 controls) and one exploratory African American samples (98 cases vs 20 controls) were analyzed to identify replicable single-nucleotide polymorphism–schizophrenia associations. The regulatory effects of risk alleles on CACNA1C messenger RNA expression were examined. The most robust risk tagSNP (rs1006737) was meta-analyzed on 17 studies (74, 122 cases vs 109, 062 controls), and associated with the gray matter volumes of seven subcortical structures in 38, 258 Europeans, and the surface areas and thickness of 34 cortical regions in 33, 992 Europeans and 2944 non-Europeans. Results: Forty-seven replicable risk single-nucleotide polymorphisms, including a 20-single-nucleotide polymorphism haplotype block, were identified in our samples (1.8 × 10 −4 ⩽ p ⩽ 0.049). This variant block was consistently associated with schizophrenia across four independent Psychiatric Genomics Consortium cohorts (79, 645 cases vs 109, 590 controls; 2.5 × 10 –17 ⩽ p ⩽ 0.017). This block showed significant expression quantitative trait loci in three independent European brain cohorts (5.1 × 10 –12 ⩽ p ⩽ 8.3 × 10 –3 ) and could be tagged by the most significant risk single-nucleotide polymorphism rs1006737. The minor allele A of rs1006737 significantly increased risk for schizophrenia across the Jewish and European samples ( p = 0.029 and 0.004, respectively), and this association was highly significant in the meta-analysis ( p = 1.62 × 10 –42 ). This allele also significantly altered the CACNA1C messenger RNA expression in five brain regions (5.1 × 10 –12 ⩽ p ⩽ 0.05), decreased the gray matter volume of thalamus ( p = 0.010), the surface area of isthmus cingulate cortex ( p = 0.013) and the thickness of transverse temporal and superior temporal sulcus cortexes (0.005 ⩽ p ⩽ 0.043). Conclusion: We identified an independent, replicable, functional, and significant risk variant block at CACNA1C for schizophrenia, which could be tagged by the most robust risk marker rs1006737, suggesting an important role of CACNA1C in the pathogenesis of schizophrenia.